Gender Inequality Against Female Online Ojek Driver (Case Study on Grab Queen Community in Malang City) - Puteri Nur Anisa Larasati; Tutik Sulistyowati; Sulismadi Sulismadi (Universitas Muhammadiyah Malang, 2021)
This study examines the gender inequality of female online motorcycle taxi drivers in the Grab Queen community in Malang City. Female online motorcycle taxi drivers in Malang City have problems from each individual who gets a case of gender inequality. The purpose of this study is to describe how the form of gender inequality that occurs in female online motorcycle taxi drivers in Malang City, especially in the Grab Queen Malang community. The research method used in writing this thesis is to use a qualitative method with a case study approach. The technique of determining the subject used snowball sampling technique. The location of this research is in the Grab Queen community, Malang City. The data collection used are interviews and documentation studies, data analysis techniques used by researchers are data reduction, data presentation, conclusing drawings or conclusions, and data validity. This study uses the concept of gender inequality, namely subordination, stereotypes, violence and double burden to classify the types of gender inequality cases and the theory used by researchers is gender functionalism from Miriam M. Johnson which consists of functions, roles, social structures, so as to achieve a balance to realize social order. From the results of theoretical analysis, there is an imbalance of roles between female and male drivers in the regulations made by partners and also the mindset of the community so that cases of inequality will easily occur among female online motorcycle taxi drivers. In this study, researchers want to examine the balance of roles to establish social order so that there is no opportunity for gender inequality.